Descriptive study of prosociality in higher education students of Colombia - Cañas Betancur, Dora Cristina; Ardila Rodríguez, William Alexander; Vásquez Caballero, Diego Andrés; Portilla Duque, Nidia (Rastros Rostros, 2023)
The goal of this study was to understand prosocial behavior in relation to sociodemographic variables in undergraduate students. We used a quantitative, non-experimental, cross-sectional, and descriptive design. Our sample consisted of 1090 male and female adults that were currently enrolled at one of many local universities. As our main instrument we used Escala de Conducta Prosocial (ECP, Auné & Attorresi, 2017), which was adapted to Colombia with adequate statistical properties for internal consistency. For the Offering Comfort subscale, it presents Cronbach’s alpha of .91 and for Offering Help it was .84. Our findings show that there are not statistically significant differences for prosocial behavior regarding: age, university type (public or private), marital status, or undergraduate program. We did find differences regarding academic semester and sex at the Offering Comfort subscale.
Keywords: social support; higher education; prosocial behavior; individual differences